The Effect Of Exselsa Coffee Roasting Temperature And Time On The Physicochemical And Sensory Properties Of Coffee Powder - Remondus Rendy R. Sihombing; Suko Priyono; Lucky Hartanti (FoodTech: Jurnal Teknologi Pangan, 2023)
This study aims to obtain the best combination of temperature and roasting time in processing excelsa coffee beans on the quality of the coffee powder produced. The research design used RAK which was arranged by factorial two factors, namely roasting temperatures of 190°C, 200°C, 210°C and roasting times of 10, 15, 20 minutes, so that 9 treatment combinations were obtained, 3 replications. The result data were analyzed statistically with the ANOVA test, followed by the BNJ test, the best quality coffee powder was produced at a temperature and time of 210°C 15 minutes, namely yield 84.70%, water content 1.85%, ash content 3.95%, caffeine content 6,88%, organoleptic characteristics, aroma 3.97 (strong), acidity 3.43 (slightly sour), body/mouthfeel 3.70 (thick), color 3.97 (black), and consumer preferences 3.70 (like).